The Developing a Learning Management Model to Enhance Complex and Systemic Thinking Skills among Preservice Physical Education Teachers Students at the Faculty of Education, Thailand National Sports University Lampang Campus - Khuana , Tanthip; Khuana, Khwanchai (Journal for Developing the Social and Community, 2026)
Background and Aims: The objective of this research was to develop and evaluate the effectiveness of a learning management model aimed at enhancing complex and systemic thinking skills among preservice physical education teachers students at the Faculty of Education, National Sports University, Lampang Campus. The sample comprised 69 second-year students enrolled in the "Learning Management Science" course during the second semester of the 2023 academic year. Participants were selected through cluster random sampling. The research instruments included: 1) a questionnaire assessing the context and needs for developing the learning management model; 2) the developed learning management model itself; 3) an assessment tool for complex thinking skills; 4) an assessment tool for systemic thinking skills; and 5) a satisfaction questionnaire. The statistics used for data analysis were means, standard deviation and t-test. Methodology: The data for this study were collected using a Research and Development (R&D) approach based on the Borg and Gall framework, consisting of four phases: (1) needs analysis, (2) model design and development, (3) quality and efficiency validation, and (4) model implementation., which was divided into three distinct phases. Phase 1: Literature Review and Needs Analysis (R1) 1. A comprehensive synthesis of relevant concepts, theories, and existing research was conducted to establish a theoretical framework for the study. 2. A needs assessment survey was administered to a non-sample group of 38 individuals to gather data on the problem and identify specific needs for developing the model. Phase 2: Draft Model Development and Refinement (D1, R2, D2) 3. A focus group meeting was held with experts to develop a draft of the learning management model aimed at enhancing complex thinking and systems thinking skills for student teachers in Physical Education, Faculty of Education, National Sports University, Lampang Campus. 4. The draft model was pilot-tested (Pilot study) (R2) with a non-sample population of 38 individuals. The data were analyzed using descriptive statistics to evaluate the model’s feasibility and initial effectiveness, leading to its improvement and revision (D2). 5. A formal critique session was organized with a panel of experts to review and finalize the learning management model based on their professional feedback. Phase 3: Implementation of the Learning Management Model (R3) 6. The final learning management model was implemented with a sample group of 69 individuals. Pre- and post-tests were administered to the group. 7. The effectiveness of the model was determined by analyzing the pre- and post-test data using a paired-samples t-test. Additionally, students’ satisfaction with the model was measured using a questionnaire, with the results analyzed using descriptive statistics. Results: 1.The problem was found to be at a moderate level, while the need for a solution was high. As a result, a learning management model to enhance complex thinking and systems thinking skills was developed for student teachers in Physical Education, Faculty of Education, National Sports University, Lampang Campus. The developed MTACS Model consists of the following five learning management stages: Stage 1: Motivation (M), Stage 2: Complex & Systems Thinking (T), Stage 3: Action/Practice (A), Stage 4: Knowledge Consolidation (C), and Stage 5: Knowledge Sharing & Dissemination (S). The model was found to be at a high level of suitability and demonstrated an efficiency of 80.04/80.09. 2. The implementation of the learning management model for enhancing complex thinking and systems thinking skills with student teachers showed the following results: 1. Students’ complex and systems thinking skills after using the model were significantly higher than before using the model, at a statistical significance level of .05. and 2. The students’ overall satisfaction with the model was at the highest level. Conclusion: The research findings can be summarized as follows: The problem was found to be at a moderate level, while the need for a solution was high. As a result, the MTACS Model learning management model was developed. The model was found to be highly suitable and demonstrated an efficiency of 80.04/80.09. The implementation of the MTACS Model was a success, as students’ complex thinking and systems thinking skills improved significantly after using it (p < .05). Furthermore, students expressed the highest level of overall satisfaction with the model. These findings suggest that the developed MTACS Model is an effective and practical approach for enhancing critical thinking skills in physical education student teachers and holds strong potential for future application in similar educational contexts.